Promoting Green Economy : Implications for Natural Resources Development, Food Security and Poverty Reduction in Africa - Nutakor, Praise; Asubonteng, Kwabena Owusu; Oku, Effiom E.; Ayuk, Elias (Book collections on Project MUSE., 2017)
Most African national economies depend on the exploitation of both renewable and non-renewable natural resources for development. Conventional and unconventional exploitation of natural resources has left negative carbon footprints. This has also degraded hotspots across the African continent, impacting negatively on people and the environment. A Green Economy offers the continent the opportunity to achieve sustained economic development devoid of environmental degradation and inefficient utilisation of natural resources. This book, Promoting Green Economy, explores issues affecting the socio-economic development of the continent and focuses on Africa's need for a green economy. With chapters written by seasoned authors from academia and industry across the continent, the book examines the challenges of sustainable management of Africa's natural resources and recommends the need for the continent to transit towards green economy as this can provide opportunities for minimising environmental footprints of all economic activities. The book calls on the commitment of the public and private sectors to the development of appropriate green economy policies and regulatory frameworks to promote inclusive growth.